Cooperative Carbon Dioxide Adsorption in Alcoholamine‐ and Alkoxyalkylamine‐Functionalized Metal–Organic Frameworks. (4th February 2020) - Mao, Victor Y.; Milner, Phillip J.; Lee, Jung‐Hoon; Forse, Alexander C.; Kim, Eugene J.; Siegelman, Rebecca L.; McGuirk, C. Michael; Zasada, Leo B.; Neaton, Jeffrey B.; Reimer, Jeffrey A.; Long, Jeffrey R.
Abstract: A series of structurally diverse alcoholamine‐ and alkoxyalkylamine‐functionalized variants of the metal–organic framework Mg2 (dobpdc) are shown to adsorb CO2 selectively via cooperative chain‐forming mechanisms. Solid‐state NMR spectra and optimized structures obtained from van der Waals‐corrected density functional theory calculations indicate that the adsorption profiles can be attributed to the formation of carbamic acid or ammonium carbamate chains that are stabilized by hydrogen bonding interactions within the framework pores. These findings significantly expand the scope of chemical functionalities that can be utilized to design cooperative CO2 adsorbents, providing further means of optimizing these powerful materials for energy‐efficient CO2 separations. Abstract : Kooperative CO2 ‐Chemisorption wurde in einem mit strukturell diversen Alkoholaminen und Alkoxyalkylaminen funktionalisierten Metall‐organischen Gerüst erreicht. Festkörper‐NMR‐Spektroskopie und DFT‐Berechnungen zeigen, dass CO2 ‐Adsorption über die Bildung und Übertragung von wasserstoffbrückenstabilisierter Carbamidsäure oder Ammoniumcarbamat‐Strukturen erfolgt.